The effect of cooperative learning model of think pair share with group advisor strategy on students' mathematics learning achievement on number pattern material - Ningsih, Wanda Suhari; Pasaribu, Laili Habibah; Harahap, Amin (Desimal: Jurnal Matematika, 2024)
This study aims to analyze the effect of the Think Pair Share (TPS) cooperative learning model combined with the Group Advisor strategy on students' mathematics learning achievement at MTs Al-Ittihad. The research method used is an experiment with a pre-post-test design in one group. Data was collected through mathematics learning achievement tests given before and after treatment, as well as interviews to obtain qualitative data about students' experiences when applying this learning model. Data analysis was conducted using a t-test to determine the difference in learning achievement before and after treatment. The results of the study show that there is a significant increase in student mathematics learning achievement after the application of the TPS model with the Group Counseling strategy. This finding shows that the application of the TPS cooperative learning model with the Group Advisor strategy is effective in improving students' mathematics learning achievement at MTs Al-Ittihad. This study provides empirical evidence that the TPS cooperative learning model with the Group Advisor strategy can be considered by teachers as an effective alternative in efforts to improve the quality of mathematics learning.